Hydrocortisone release from tablets based on bioresorbable poly(ether-ester-urethane)s (Brazilian Journal of Pharmaceutical Sciences, 2017)
Bioresorbable linear poly(ether-ester-urethane)s with different hydrophilic characteristics were synthesized from triblock copolymers of poly(ε-caprolactone)-poly(ethylene oxide)-poly(ε-caprolactone) (PCL-PEO) as macrodiols, and L-lysine diisocyanate (LDI) or hexamethylenediisocyanate (HDI) were used as the required diisocyanates. Macrodiols were obtained by ring-opening polymerization (ROP) of ε-caprolactone (CL). Polyurethanes were synthesized by the reaction of the triblock copolymers with LDI or HDI in solution using stannous 2-ethylhexanoate as catalyst. Polyurethane tablets were fabricated and investigated as prospective drug delivery systems. The effect of the PEO content on the polymers' performance as drug carriers was evaluated. It was found that water provoked more swelling and erosion of polymers with higher contents of PEO. The hydrocortisone release profiles were analyzed using the Ritger-Peppas approximation. An anomalous release behaviour (values of n higher than 0.5) was found for most of the analyzed samples.